Nanomedicine for Global Health. (December 2014) - Tsai, Nathaniel; Lee, Bryan; Kim, Austin; Yang, Richard; Pan, Ricky; Lee, Dong-Keun; Chow, Edward K.; Ho, Dean
Despite modern advances, a broad range of disorders such as cancer and infectious diseases continually afflict the global population. Novel therapeutics are continuously being explored to address these challenges. Therefore, scalable, effective, and safe therapies that are readily accessible to third-world countries are of major interest. In this article, we discuss the potential advantages that the nanomedicine field may harness toward successful implementation against some of the major diseases of our generation.